Ղրիմահայ բանաստեղծներ (ԺԴ.-ԺԷ. դարեր) - Հենրիկ Բախչինյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В XIV-XVII веках в армянской общине Крыма процветала культура, особенно поэзия. Армянские поэты Крыма либо мигрировали из Армении, либо уже родились там, либо временно посещали полуостров. Их произведенияохватывали не только традиционные темы армянской средневековой поэзии, но и отражали внутреннюю жизнь Крыма, исторические события и состояние местной армянской общины. Такие сочинения также ценны для изучения истории Крыма.In the 14th-17th centuries, the Armenian cultural and educational life, particularly the poetry, has fl ourished in the Crimea. The Crimean Armenian poets were either migrated from Armenia or were already born there, or have visited the peninsula temporarily. Their works have not only touched the traditional themes of the Armenian medieval poetry, but also refl ected the internal life of Crimea, historical events, and the state of local Armenian community. Such works are also valuable for studying the Crimean history.
Keywords: History; Biography; Auxiliary Sciences of History; Armenian Diaspora